Analogy in the Mechanism of Judicial Control over the ‘Golden Parachutes’ Amount - MIKRYUKOV, Viktor A, (Journal of Advanced Research in Law and Economics; Vol 8 No 3 (2017): JARLE Volume VIII Issue 3(25) Summer 2017, 2017)
This article argues the support of judicial control over the amount of compensation payments for early dismissal of managers (their deputies and chief accountants) of organizations in cases when such dismissal occurs in the absence of the guilty behavior of the employee in connection with the change of the legal body property owner or the organization controlling the group of its participants (shareholders). The author substantiates the advantages of using the analogy method and the use of worked civil legal mechanisms within the framework of abnormal labor relations, but insists on the necessity of normative filling of the existing gap by introducing amendments to the Labor Code of the Russian Federation.